Macrophages in Organ Transplantation - Ordikhani, Farideh; Pothula, Venu; Sanchez-Tarjuelo, Rodrigo; Jordan, Stefan; Ochando, Jordi (Frontiers in Immunology, 2020)
Current immunosuppressive therapy has led to excellent short-term survival rates in organ transplantation. However, long-term graft survival rates are suboptimal, and a vast number of allografts are gradually lost in the clinic. An increasing number of animal and clinical studies have demonstrated that monocytes and macrophages play a pivotal role in graft rejection, as these mononuclear phagocytic cells recognize alloantigens and trigger an inflammatory cascade that activate the adaptive immune response. Moreover, recent studies suggest that monocytes acquire a feature of memory recall response that is associated with a potent immune response. This form of memory is called “trained immunity,” and it is retained by mechanisms of epigenetic and metabolic changes in innate immune cells after exposure to particular ligands, which have a direct impact in allograft rejection. In this review article, we highlight the role of monocytes and macrophages in organ transplantation and summarize therapeutic approaches to promote tolerance through manipulation of monocytes and macrophages. These strategies may open new therapeutic opportunities to increase long-term transplant survival rates in the clinic.